Decarbonising the portland and other cements—via simultaneous feedstock recycling and carbon conversions sans external catalysts - Devasahayam, Sheila (MDPI, 2021)
The current overarching global environmental crisis relates to high carbon footprint in cement production, waste plastic accumulation, and growing future energy demands. A simultaneous solution to the above crises was examined in this work. The present study focused on decarbonizing the calcination process of the cement making using waste plastics and biowastes as the reactants or the feedstock, to reduce the carbon footprint and to simultaneously convert it into clean energy, which were never reported before. Other studies reported the use of waste plastics and biowastes as fuel in cement kilns, applicable to the entire cement making process. Calcination of calcium carbonate and magnesium carbonate is the most emission intensive process in cement making in Portland cements and Novacem-like cements. In the Novacem process, which is based on magnesium oxide and magnesium carbonates systems, the carbon dioxide generated is recycled to carbonate magnesium silicates at elevated temperatures and pressures. The present study examined the Novacem-like cement system but in the presence of waste plastics and biomass during the calcination. The carbon dioxide and the methane produced during calcination were converted into syngas or hydrogen in Novacem-like cements. It was established that carbon dioxide and methane emissions were reduced by approximately 99% when plastics and biowastes were added as additives or feedstock during the calcination, which were converted into syngas and/or hydrogen. The reaction intermediates of calcination reactions (calcium carbonate–calcium oxide or magnesium carbonate–magnesium oxide systems) can facilitate the endothermic carbon conversion reactions to syngas or hydrogen acting as non-soot forming catalysts. The conventional catalysts used in carbon conversion reactions are expensive and susceptible to carbon fouling. Two criteria were established in this study: first, to reduce the carbon dioxide/methane emissions during calcination; second, to simultaneously convert the carbon dioxide and methane to hydrogen. Reduction and conversion of carbon dioxide and methane emissions were facilitated by co-gasification of plastics and bio-wastes.